ISOLATION, MANUFATURE AND QUALITATIVE TEST OF CELLULOSE MICROCRYSTALLIZATION POWDER FROM KETAPANG LEAVES (TERMINALIA CATAPPA L.) USING CHEMICAL DELIGNIFICATION AND HYDROLISIS METHODS - YUSPA; MUHAMMAD; FATIMAH; MAULIDAH, NUR; LUTHFIA, RA’IDAH; LESTARI, YULIANITA PRATIWI INDAH (International Journal of Applied Pharmaceutics, 2025)
Objective: This study aimed to synthesize and characterize Microcrystalline Cellulose (MCC) from ketapang leaves (Terminalia catappa L.) and compare it with commercial Avicel PH 102. Methods: Ketapang leaves underwent delignification using sodium hydroxide (NaOH), followed by acid hydrolysis using optimized Hydrochloric Acid (HCl) concentrations. The resulting Microcrystalline Cellulose (MCC) was characterized through color reaction; organoleptic, solubility, pH, melting point, microscopic, and fourier transform infrared spectroscopy analyses, with Avicel PH 102 as the comparator. Results: The α-cellulose yield from ketapang leaves was 24.13%, and Microcrystalline Cellulose (MCC) yield reached 83.70%. Hydrochloric Acid (HCl) 1 M gave the highest Microcrystalline Cellulose (MCC) yield of 96%. Microcrystalline Cellulose Ketapang Leaves (MCCKL) was a yellowish-white, odorless, tasteless crystalline powder, similar to Avicel PH 102. It was insoluble in water, alcohol, ether, and acids/bases, meeting Microcrystalline Cellulose (MCC) standards. The pH was 6.47 (standard: 5.0–7.5), and the melting point was 262 °C, comparable to Avicel PH 102. Microscopically, Microcrystalline Cellulose Ketapang Leaves (MCCKL) fibers appeared longer and larger but remained suitable as tablet excipients. Fourier Transform Infrared (FTIR) spectroscopy confirmed the presence of O-H, C-H, C-OH, and β-glycoside groups, indicating structural similarity to commercial Microcrystalline Cellulose (MCC). Conclusion: This study demonstrates the successful synthesis of Microcrystalline Cellulose (MCC) from ketapang leaves with an 83.70% yield from 24.13% α-cellulose. The resulting Microcrystalline Cellulose Ketapang Leaves (MCCKL) showed comparable physicochemical properties to commercial Microcrystalline Cellulose (MCC) (Avicel PH 102), including pH, solubility, melting point, and functional groups. Additional tests showed favorable values for flow rate, moisture content, and compressibility, suggesting that Microcrystalline Cellulose Ketapang Leaves (MCCKL) has strong potential as a direct compression tablet filler.